The Statewide Epidemiology of Mucormycosis Among Trauma Patients in Florida. Issue 4 (April 2023) - Clark, Jason Michael; Liu, Huazhi; Collins, Susan; Watson, Carrie; Ferber, Laurence; Richards, Winston T.; Taylor, Dana; Ang, Darwin N.
Objectives: Mucormycosis is a rare angioinvasive infection caused by filamentous fungi with a high lethality among the immunocompromised. In healthy people, the innate immune system is sufficient to prevent infection. The exception to this is deep tissue exposure seen during trauma. The purpose of this study is to evaluate the epidemiology of mucormycosis using a statewide population-based data set. Methods: This is a retrospective cohort study of all hospital admissions for mucormycosis within the state of Florida from 1997 through the beginning of 2020. A distribution map was created to evaluate for geographic variation. Botanical growth zones, based on plant hardiness, used by state environmental agencies and landscapers were also used to detect possible patterns based on climate conditions throughout Florida. A multivariable regression analysis was performed to account for confounders and limit bias. Results: A total of 1190 patients were identified for mucormycosis infection. Only 86 of these patients were admitted for trauma. Cutaneous infections were more prevalent among trauma patients while non-trauma patients had more pulmonary infections ( P = .04). Trauma patients with infection tended to be younger and less likely to suffer from comorbidities such as immunosuppression (36% vs 46%, P = .07) and diabetes (22.1% vs 47.1%, P ≤ .0001) as compared to their non-trauma counterparts. Mortality was similar with 17.8% for non-trauma patients and 15.1% for traumatized patients (AOR .80 [.42, 1.52]). Length of stay was longer for trauma patients (37.3 vs 23.0, P < .0001). Infections were less prominent in plant hardiness Zone 9 and Zone 10 as compared to Zone 8 (AOR .71 [.61, .82]; AOR .54 [.46, .64], respectively). Conclusion: Trauma patients who develop infection from mucormycosis are at high risk of death despite being a younger and healthier population. Mucormycosis infections were primarily soft tissue based among trauma patients. These infections are more prevalent in colder regions within Florida.